Respon Siswa Terhadap Penggunaan Gamifikasi dengan Classpoint pada Pembelajaran Berbasis Proyek Materi Geografi Keragaman Budaya Indonesia - Safitri Pramei Hastuti; Sriyanto Sriyanto (UM Purwokerto Press, 2023)
The problem faced during learning is learning that is focused on educators (teacher-centered) or with the lecture method. As a result, students cannot master 21st-century skills optimally. This research aimsÂ to see students' responses to learning geography on project-based cultural diversity material (PJBL) and to make it more interactive students were given assessments in the form of quizzes using Classpoint media with gamification. This study uses descriptive quantitative research to analyze students' views on the use of Classpoint as an interactive learning medium. Data was collected through a questionnaire instrument consisting of 8 statement items spread over four sections, namely about project-based learning, the use of Classpoint, and project-based learning with Classpoint and constraints on using Classpoint. This statement was distributed to respondents, namely students of class XI IPS SMA Muhammadiyah Sokaraja. By using gamification in Classpoint on project-based geography learning, cultural diversity material received a good response from students, namely agreeing with the application of this learning. Student engagement also increases by using Classpoint gamification in learning. This is because Classpoint provides many features that can be gamified which encourages students to be more interactive so that students feel challenged to work on the questions and it is hoped that students understand more about the material being taught.. There are many advantages to using Classpoint media, namely, students become more active, but there are weaknesses if the internet network is unstable, it will prevent the quiz given by the teacher from being sent.